Phylogenetic Relationships among Virulent Newcastle Disease Virus Isolates from the 2002-2003 Outbreak in California and Other Recent Outbreaks in North America - Pedersen, Janice C. (American Society for Microbiology, 2004)
Isolates from the 2002-2003 virulent Newcastle disease virus (v-NDV) outbreak in southern California, Nevada, Arizona, and Texas in the United States were compared to each other along with recent v-NDV isolates from Mexico and Central America and reference avian paramyxovirus type 1 strains. Nucleotide sequencing and phylogenetic analyses were conducted on a 1,195-base genomic segment composing the 3′ region of the matrix (M) protein gene and a 5′ portion of the fusion (F) protein gene including the M-F intergenic region. This encompasses coding sequences for the nuclear localization signal of the M protein and the F protein cleavage activation site. A dibasic amino acid motif was present at the predicted F protein cleavage activation site in all v-NDVs, including the California 2002-2003, Arizona, Nevada, Texas, Mexico, and Central America isolates. Phylogenetic analyses demonstrated that the California 2002-2003, Arizona, Nevada, and Texas viruses were most closely related to isolates from Mexico and Central America. An isolate from Texas obtained during 2003 appeared to represent a separate introduction of v-NDV into the United States, as this virus was even more closely related to the Mexico 2000 isolates than the California, Arizona, and Nevada viruses. The close phylogenetic relationship between the recent 2002-2003 U.S. v-NDV isolates and those viruses from countries geographically close to the United States warrants continued surveillance of commercial and noncommercial poultry for early detection of highly virulent NDV.